Florida Dairy Farm Situation and Outlook 2003 - Russ Giesy; Albert De Vries; Michael Zylstra; Richard Kilmer; Dave Bray; Dan Webb (EDIS, 2003)
This document is AN138, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2003.